Farmers perspectives towards the rehabilitation and subsequent interventions by the LDA in the irrigation schemes in Sekhukhune District - Nowata, Matsoba Sandile Jethro (University of Limpopo (Turfloop Campus), 2014)
Small-scale irrigation farming has been found to have potential to improve agricultural production of the small-scale farmers and thereby improving their livelihoods. The Government of South Africa through the RESIS programme embarked on a project to increase agricultural production through investment in new or existing small scale irrigation schemes. Contrary to expectations, most of the government supported irrigation schemes have failed to meet the expectations of both government and farmers. The objectives of this study was to determine the perceived reasons for the failure of the irrigation schemes and determine the association between socio-economic characteristic of farmers and the perceived reasons for these schemes. Farmers who participated in the scheme or had participated (in the case of failed/dysfunctional schemes) in the RESIS irrigation schemes were randomly sampled and interviewed. Multinomial regression analysis was used to determine the association between farmers’ socio-economic profiles and their perceptions on the reasons for the failure of the schemes. According to farmers’ ranking, economic, competition and socio-cultural factors were perceived as having a large influence on the success of the schemes. Climate/ecological and technological factors were cited as having lesser influence on the success of the schemes. Socio-economic characteristics (literacy level, age, education level) of farmers and number of beneficiaries in a scheme had influence on how farmers perceive the influence of economic, competition, socio-cultural, technological, climate and administrative/management factors.. The strategic partnership model was generally found to encourage dependency and thus discouraging the sense of ownership. The findings revealed the importance of considering the socio-economic circumstances of farmers in future planning of the irrigation schemes to enhance the success of these schemes. The findings may also have implications for other government supported projects that involve communities with diverse needs and socio-economic profiles.
Thesis (M.Sc (Agriculture)) -- University of Limpopo, 2014
Keywords: Irrigation Schemes; Irrigation Farming; Agriculture; Sekhukhune District; Irrigation farming - South Africa; Farms, Small